When Instability Increases The Effectiveness of Aid Projects - Guillaumont, Patrick; Laajaj, Rachid (The World Bank, 2006)
The authors assess the effect of economic instability on the success of projects funded by the World Bank using the outcome of the projects, which is a notation of their overall success determined by the Bank's Independent Evaluation Group. It has been argued in macroeconomic studies that aid effectiveness is higher in vulnerable countries because it dampens the negative effects of shocks. The authors show that this finding is not inconsistent with the observation that the success of the projects is lower in an unstable environment. Instability, in particular the instability of exports, harms aid projects as it harms the rest of the economy, while the success of projects decreases when the total amount of aid received increases, due to absorptive capacity limitations. But this decrease is slower when instability is higher, showing a positive effect of aid through its stabilizing impact. The authors find the same results keeping only the projects funded by nonconcessionary loans, which suggests that the cushioning effect of aid extends not only to aid funded projects but to whole sets of projects. Corroborating macroeconomic findings, their results lead to the same conclusion that more aid should be allocated to more vulnerable countries, in spite of the lower success of the projects in an unstable environment: project evaluations cannot include the macrostabilizing effect of the aid delivered through projects